2022
DOI: 10.1017/jfm.2022.705
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of a collapsing bubble in contact with a rigid wall

Abstract: This work reveals that the dynamic response of a spherical cap bubble in contact with a rigid wall depends on the effective contact angle at the instant prior to collapse. This parameter allows us to discriminate between two regimes in which the mechanisms of interaction between the collapsing bubble and its surrounding medium differ significantly: when the contact angle is smaller than $90^{\circ }$ , a classical jet directed towards the wall is observed, whereas if the initial cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…(2012) and Aganin, Kosolapova & Malakhov (2019), and was later shown to occur for axisymmetric cap-shaped bubbles in simulations and experiments by Saini et al. (2022). Here, a high-pressure region below the bubble forms that accelerates a liquid jet flow away from the surface.…”
Section: Introductionmentioning
confidence: 90%
“…(2012) and Aganin, Kosolapova & Malakhov (2019), and was later shown to occur for axisymmetric cap-shaped bubbles in simulations and experiments by Saini et al. (2022). Here, a high-pressure region below the bubble forms that accelerates a liquid jet flow away from the surface.…”
Section: Introductionmentioning
confidence: 90%
“…Bubble dynamics in an infinite/semi-infinite liquid domain has been widely and extensively studied in the literature, including interactions with rigid walls (Hsiao et al 2014;Brujan et al 2018;Saini et al 2022;Zeng, An & Ohl 2022;Zhang et al 2023a), a water-air free surface (Kang & Cho 2019;Bempedelis et al 2021;Saade et al 2021;Cerbus et al 2022), elastic boundaries (Brujan et al 2001;Klaseboer & Khoo 2004b), fluid-fluid interfaces (Klaseboer & Khoo 2004a;Orthaber et al 2020), adjacent bubbles (Han et al 2016;Tomita & Sato 2017;Luo, Xu & Khoo 2021), suspended particles (Poulain et al 2015;Ren et al 2022) and more. Of particular interest are the bubble collapse patterns and jetting behaviours in different situations.…”
Section: Introductionmentioning
confidence: 99%
“…2018; Saini et al. 2022; Zeng, An & Ohl 2022; Zhang et al. 2023 a ), a water–air free surface (Kang & Cho 2019; Bempedelis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fuster, Pham & Zaleski (2014) discussed the stability of bubbly liquids from a free energy perspective and extended these ideas to clusters of bubbles. Saini, Zaleski & Fuster (2021) and Saini (2022) discussed the effect of wall boundary condition on the stability of spherical cap shaped nuclei attached to a rigid wall and showed that pinning can stabilize the bubble nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…There are several other studies available in the literature, but there is no common consensus for the structure and the growth of the microlayer (Jung & Kim 2018;Zou, Gupta & Maroo 2018;Sinha, Narayan & Srivastava 2022). In the cavitation process, microlayer formation influences the bubble shape at the maximum volume, which is an important parameter that afterwards governs the collapse dynamics (Saini et al 2022).…”
Section: Introductionmentioning
confidence: 99%